2003
DOI: 10.1348/135910703321649178
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions, mood and coping in predicting attendance at cardiac rehabilitation

Abstract: Attenders and poor/non-attenders at CR were distinguished by illness representations, distress and usage of coping strategies. The variables found to be the best predictors of attendance could be used to screen those unlikely to attend and to develop interventions for enhancing attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 15 publications
7
98
1
1
Order By: Relevance
“…However, this does not explain why the average depression level is even lower among the remaining patients than in the general population. Furthermore, the mean HADS scores obtained in this investigation are similar to those reported in other studies with cardiac patients [34,35,36]. It is more likely that some kind of response shift or change of frame of reference has taken place.…”
Section: Discussionsupporting
confidence: 88%
“…However, this does not explain why the average depression level is even lower among the remaining patients than in the general population. Furthermore, the mean HADS scores obtained in this investigation are similar to those reported in other studies with cardiac patients [34,35,36]. It is more likely that some kind of response shift or change of frame of reference has taken place.…”
Section: Discussionsupporting
confidence: 88%
“…Killaspy et al 191 is one of several studies 8,192,193 that demonstrates that non-attendance at psychiatric services is related to increased pathology and greater need, and serves as a corrective to suggestions that non-attenders may self-select because they do not need to be seen.…”
Section: Roberts Et Almentioning
confidence: 99%
“…At 6-and 12-month follow-ups, physical health (measured by evidence of comorbidities or overall physical health status) and mental health (measured by evidence of depressive symptoms or mental health status) directly influences attendance at treatment visits. Whitmarsh et al 193 investigated psychological variables predicting poor attendance or non-attendance at cardiac rehabilitation. Using multivariate analysis they found that poor/non-attenders at cardiac rehabilitation were distinguished by illness representations, distress and usage of coping strategies.…”
Section: Roberts Et Almentioning
confidence: 99%
“…Better attendance to rehabilitation has been related to a stronger belief in the controllability of heart disease [19][20][21], less perceived symptoms associated with heart disease [21], and attribution of own heart disease to life style factors [20]. A slower return to work and resumption of social and domestic duties has been related to more negative perceived consequences of MI [19].…”
Section: Introductionmentioning
confidence: 99%